Imaging cilia in Drosophila melanogaster. - Vieillard, J.; Duteyrat, J.L.; Cortier, E.; Durand, B. (Methods in Cell Biology, 2015)
Drosophila melanogaster is a powerful genetic model organism to understand the function of proteins in specific cellular processes. Cilia have been extensively studied in Drosophila playing various sensory functions that are essential for fly survival. Indeed, flies defective in cilia formation cannot walk, fly, or feed properly. Drosophila harbors different types of cilia that can be motile or immotile or that can show compartimentalized (intraflagellar transport (IFT)-dependent) or cytoplasmic (IFT-independent) mode of assembly. Therefore, Drosophila represents an advantageous model organism to study the function of novel ciliary candidates and to address specific questions such as their requirement for IFT-dependent processes versus other aspects of cilia-associated functions. This chapter describes protocols to visualize cilia by direct or indirect fluorescent labeling and protocols to analyze ciliary ultrastructure by electron microscopy.